Real-World Nuclear Deterrence : the Making of International Strategy - Coleman, David G. and Siracusa, Joseph M. (London Pentagon Press, 2008)
Shows how nuclear deterrence has worked rather than how theorists say it should work. This work also shows how nuclear proliferation threatens to create a far more complicated international situation as the number of states with nuclear deterrents grows. It puts some of the important problems of nuclear deterrence into global context.
Include Index and Bibliography
Keywords: Nuclear disarmament -- Security, International